Residents’ Overall Quality of Life in Smart Tourism Destination in Zhuhai, China - Zitao, Liu; Rahmanita, Myrza; Ingkadijaya, Rahmat; Rahayu, Nurti (Institut Pariwisata Trisakti, 2025)
Smart tourism destinations (STDs) aim to improve the travelers’ experience and the local residents’ quality of life. However, existing research mainly focuses on the perspectives of tourists and ignores the attitudes of residents. Residents' attitudes signify their support for local smart tourism development. Without residents' support, STD-related projects may experience failure. This study fills this gap by exploring how perceived impact of smart travel/tourism (IST) and sense of leisure of well-being (SLW) contributed to residents’ overall quality of life (QoL). This study adopts quantitative method with questionnaire. The finding confirms the residents’ positive impact on smart travel/tourism in Zhuhai, China. Similarly, they residents also showed their approval on the leisure well-being. Additionally, the findings highlight significant relationships between the perceived impact of smart travel/tourism (X1), sense of leisure well-being (X2), and overall quality of life (Y). Residents' quality of life is significantly improved by positive perceptions of smart tourism impacts and leisure well-being. This underscores the importance of the local perspective in STD success. STD initiatives should prioritize enhancing these specific aspects for residents. This paper suggests that engaging the community and focusing on their perceived benefits regarding smart travel and leisure well-being will foster crucial support and ensure project viability. Keywords: overall quality of life, smart travel, leisure well-being, residents’ attitudes, smart tourism destination